2020
DOI: 10.1088/1755-1315/425/1/012055
|View full text |Cite
|
Sign up to set email alerts
|

Morphological characteristics and yields of several sweet potato (Ipomoea batatas L.) tubers

Abstract: This study aims to evaluate certain tubers of new sweet potato clones for their morphological characters of and yield under low input conditions in the middle highland. This study was conducted at Saree, Aceh Besar, the Province of Aceh (485 m ASL) from February to July 2015. The study used a Completely Randomized Block Design of non-factorial with 12 sweet potato clones consisting of nine clones passed by CIP-SEA Bogor, Indonesia (CIP-LSQ, CIP-1945, CIP-MAN, CIP-513, CIP-BDG, CIP-WHI-5, CIP-W86P, CIP-B9, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
9
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 15 publications
4
9
0
1
Order By: Relevance
“…Differences in sweet potato yields can be influenced by genetic conditions of the plant, the environment in which cultivation is carried out, the technical culture applied. The results of this study are in line with [5] who found that the effect of genotype, environment or genotype interaction with the environment was significant on sweet potato yields.…”
Section: Parameters Of Sweet Potato Yieldsupporting
confidence: 91%
See 1 more Smart Citation
“…Differences in sweet potato yields can be influenced by genetic conditions of the plant, the environment in which cultivation is carried out, the technical culture applied. The results of this study are in line with [5] who found that the effect of genotype, environment or genotype interaction with the environment was significant on sweet potato yields.…”
Section: Parameters Of Sweet Potato Yieldsupporting
confidence: 91%
“…To get the best sweet potato production, it is very important to choose varieties that are suitable for environmental conditions. [5]. This study aims to determine the potential for growth and production of local genotypes of sweet potato if cultivated in a different location from the area of origin and the response to rice straw compost.…”
Section: Introductionmentioning
confidence: 99%
“…The results of our study are close to the findings of Kareem (2013) where the yield of storage roots of different genotypes of sweetpotato ranged from 5.43 to 10.90 t ha -1 . We also observed the correlation of higher tuber fresh weight with higher tuber yield that was reported by Hayati et al (2020) and Hossain et al (2018).…”
Section: Yield Of Storage Rootssupporting
confidence: 89%
“…That's why its cultivation could not reach its maximum yield potential, resulting in lower yield production. The morphological and yield contributing characteristics like leaf area, leaf production, leaf photosynthesis, tuber formation and development, total dry matter production, and tuber yield depend on genetic and environmental factors (Hayati et al, 2020). For improving sweet potato varieties, the analysis of genotypes at the genetic level with agro-morphological traits (Mahmud et al, 2021;Rosero et al, 2020) can provide more information that will be helpful for the plant breeders.…”
Section: Althoughmentioning
confidence: 99%
See 1 more Smart Citation